Pembuatan Logo sebagai Branding Produk pada UMKM Keripik Ibu Titi berdasarkan Perspektif Islam di Desa Wates Jaya - Damayanti, Agustina; Husna Asri, Kholifatul; Malikur Rahmat, Faridudin (ALIF: Sharia Economics Journal, 2024)
Tight business competition requires every business to implement strategies in product marketing to gain a competitive advantage. One strategy to increase consumer buying interest is the application of Branding to products. Branding is an activity to create an image for a product. Brands have an important role in supporting the success of MSMEs in developing their business. As for Branding in Islam, it is based on sharia principles, one of which is the presence of halal labels and packaging and in accordance with sharia principles, which brings out many values such as honesty, respect for accountability and a core understanding of sharia principles. Main elements in building a brand is a logo. A creative logo can make consumers interested in buying products from these MSME players. In an effort to attract product selling value, MSME players must continue to innovate and be creative to improve the quality of their products. Mother’s Chips UMKM Titi is one of the MSMEs in Wates Jaya Village. Even though it has been around for a long time, this MSME does not have a logo for its business at all. Seeing this problem, this activity aims to create a visual identity for Ibu Titi Chips UMKM through a logo Branding process. Making the logo was considered appropriate because it was in accordance with the business conditions required by Mrs. Titi’s Chips UMKM. The method used in this service begins with conducting a survey on Mrs. Titi Chips MSMEs by conducting interviews, analyzing business needs, and submitting logo results. The result of this service activity is the presence of a visual identity through a logo for the packaging of Ibu Titi Chips products.